DARI YADNYA KE PENCITRAAN: PERGESERAN NILAI PENDIDIKAN AGAMA HINDU DI ERA EKSISTENSI DIGITAL - Ni Putu Ratna Pratiwi (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
The development of digital technology and social media has influenced how Hindu communities practice and express their religiosity. Religious activities that were once primarily spiritual and communal are now increasingly displayed in digital spaces. This study aims to analyze the shift in Hindu Religious Education values in the era of digital existence, particularly the transformation of yadnya practices from spiritual devotion to social image construction. The study employed a qualitative approach with a descriptive-critical design. Data were collected through digital observation, in-depth interviews, documentation, and literature review. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings show that social media has become a new arena for constructing religious identity among Hindus. Yadnya practices, which are rooted in the values of śraddhā, bhakti, and sincerity, have undergone a shift in meaning when displayed on social media that emphasizes visibility and public recognition. The study found a tendency to shift from value internalization to value representation, where religiosity is not only experienced spiritually but also presented as a public identity. Therefore, strengthening religious digital literacy and character education based on Hindu values is necessary to preserve spiritual authenticity amid the growth of digital culture.